Influência da formação de hidroxialuminosilicatos na biodisponibilidade do alumínio - Noremberg, Simone Moraes da Silva (2010)
Solutions for parenteral nutrition may be contaminated by aluminum and silicate due to their storage in containers made of glass and due to the sterilization process (autoclave), which promotes the lixiviation of these glass constituents into the solution. The simultaneous presence of Al and silicate may lead to the formation of insoluble hydroxyaluminosilicates and the formation of particulate matter in solution. The presence of particulate matter in solutions for parenteral administration should be controlled because of the risk posed to the patients, thus, pharmacopoeias and regulatory agencies, limit the particle size to 10 Om e 25 Om in a determined volume of solution. In this study, the method of membrane filtration was used to investigate the distribution profile of particles, considering their size, in solutions containing Al (0.5 mg/L) and silicate (0.5; 1.0; 5.0; 10; and 20 mg/L), in the presence or not of 2% calcium gluconate or 1 M potassium dihydrogenphosphate (parenteral solutions presenting the highest contamination by Al and silicate). After 24 h, 1, 2, 3, and 6 months the solutions were prepared, aliquots of 2 mL were filtered in membranes of 0.1; 0.2; and 0.45 Om, and the Al and silicate were measured in the filtrates by graphite furnace atomic absorption spectrometry (GF-AAS). The interference of silicon on the Al measurement by GF-AAS was investigated, and pyrolysis and atomization temperatures were optimized. For Si measurement, chemical modifiers, such as Pd+Mg, Pd only, CaCl2 and Pd+Ca, were tested, and pyrolysis and atomization temperatures were also optimized. Particle sizes as well as their distribution as a percentage were also measured. The formation of hydroxyaluminosilicates was observed in solutions containing 0.5 mg/L Al and silicate in a concentration ≥ 10 mg/L, since for these conditions Al was not retained by the membranes. Particle size distribution confirmed this result, as the particles formed in the presence of a higher concentration of silicate (20 mg/L) were between 0.011 e 0.1 Om. Differently, particles formed in solutions with lower silicate concentration were retained by the membranes. In the presence of calcium gluconate or potassium dihydrogenphosphate it was not possible to observe the formation of hydroxyaluminosilicates. Nevertheless, it was possible to verify that the size of the particles in these solutions was not bigger than the recommended by the regulatory agencies.